THE ANALYSIS OF THE STUDENTS ENGLISH SPEAKING ABILITY IN CLASS X AUTOMOTIVE ENGINEERING 1 AT SMK N 3 BANGLI - Purnami, Ni Made Ayu; Juniartini, Ni Putu Ayu; Janawati, Desak Putu Anom (Institut Pendidikan Tapanuli Selatan, 2025)
Quintessentially, the process of interaction between student and educator, which is supported by learning resources in a particular learning environment is called the process of learning. Learning English brings crucial influence, furthermore it is ​​utilized widely in various fields including education, commerce, knowledge, legal system, tourism sector, international diplomacy, technology, and various other aspects it has been recognized. Thereupon, developing proficiency in speaking English and communicating effectively and efficiently are the main purpose of language learning. Furthermore, this research aimed to find out and explain how to analyze students' English-speaking skills in class X Automotive Engineering 1 at SMK N 3 Bangli. This study method used a qualitative research method. The subjects of this research were class X Automotive Engineering 1 students at SMKN 3 Bangli. In this research, the data collection methods used were interviews and questionnaires. Based on the results of research, there are several conclusions that can be obtained, namely that students show generally positive responses, students participate actively and express their enthusiasm in learning English. This research highlighted various factors that influence students' English learning experiences, including fear of assessment, the importance of positive feedback, and the impact of different teaching methods.